2021
DOI: 10.1016/j.heliyon.2021.e08479
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta-analysis on prevalence and epidemiological risk factors of zoonotic Fascioliasis infection among the ruminants in Bangladesh

Abstract: The parasitic Fascioliasis is a zoonotic and economically significant disease for livestock and humans, creating public health concerns around the world, including in Bangladesh. Populations of Bangladesh are more vulnerable to this parasitic infestation for their intimate interactions. To tackles the adverse effects on humans from food animals, it is exigency to know the exact prevalence and associated risk factors of zoonotic Fascioliasis among ruminants. Therefore, the aim of this systematic review and meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 38 publications
2
4
0
1
Order By: Relevance
“…The results showed that sheep had higher (34.74%) rates of infection with fasciolosis than goats (25.41%). These results are consistent with the study of Mia et al [35]. The lifestyles of sheep and goats are different.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The results showed that sheep had higher (34.74%) rates of infection with fasciolosis than goats (25.41%). These results are consistent with the study of Mia et al [35]. The lifestyles of sheep and goats are different.…”
Section: Discussionsupporting
confidence: 93%
“…The prevalence of females (48.33%) was higher than males (29.54%) This result is similar to the study in Bangladesh. The reason is that high stress during the parturition period may decrease individual immunity, the one with lower immunity may infect disease more susceptibility [35]. Thus, more attention should be paid to monitoring female animals for promoting the prevention and control of fasciolosis.…”
Section: Discussionmentioning
confidence: 99%
“…The study of climatic factors showed that there were significant positive correlations between cattle fascioliasis and rainfall and humidity and negative correlations with evaporation. These results were in agreement with a systematic review on prevalence and epidemiological risk factors of fascioliasis in Bangladesh, which reported a higher prevalence in the rainy season [ 22 ]. During the rainy season, the watery area and humidity favours the growth of snails, which are intermediate hosts for the miracidia to develop into cercariae.…”
Section: Discussionsupporting
confidence: 92%
“…Infestasi Fasciola sp. pada sapi perlu diperhatikan karena bersifat zoonosis dan menular cepat terutama pada sapi dengan konsumsi pakan hijauan alami tercemar metaserkaria (Mehmood et al, 2017;Mia et al, 2021). Metaserkaria merupakan fase infektif dari parasit kelas Trematoda yang apabila termakan oleh ternak akan menyebabkan infeksi.…”
Section: Pemeriksaan Sampel Fesesunclassified